Prevalence of Overweight and Obesity in Adolescents: A Systematic Review. (26th June 2013) - Bibiloni, Maria del Mar; Pons, Antoni; Tur, Josep A.
Abstract : Objective . To review the extant literature on the prevalence of overweight and obesity in adolescents (10–19 years old) of both sexes. Design . The search was carried out using Medline and Scopus considering articles published from the establishment of the databanks until June 7, 2012. Data on the prevalence of children being overweight and obese from the International Obesity Task Force (IOTF) website was also reviewed. Only original articles and one National Health Report were considered. Forty studies met the inclusion criteria. Results . Twenty-five of these studies were nationally representative, and ten countries were represented only by regional data. Conclusions . The prevalence of overweight and obesity among adolescents worldwide is high, and obesity is higher among boys. The IOTF criterion is the most frequently used method to classify adolescents as overweighed or obese in public health research.